The fact of resonance modernist acoustics and narrative form - Napolin, Julie Beth 1978- (Idiom: inventing writing theory, 2020)
The Fact of Resonance returns to the colonial and technological contexts in which theories of the novel developed, seeking in sound an alternative premise for theorizing modernist narrative form. The book shows how the experience of reading is undergirded by the sonic